A comparison of exogenous promoter activity at the ROSA26 locus using a ΦiC31 integrase mediated cassette exchange approach in mouse ES cells. - Chiann-mun Chen; Jon Krohn; Shoumo Bhattacharya; Benjamin Davies (PLoS ONE)
The activities of nine ubiquitous promoters (ROSA26, CAG, CMV, CMVd1, UbC, EF1α, PGK, chicken β-actin and MC1) have been quantified and compared in mouse embryonic stem cells. To avoid the high variation in transgene expression which results from uncontrolled copy number and chromosomal position effects when using random insertion based transgenic approaches, we have adopted a PhiC31 integrase mediated cassette exchange method for the efficient insertion of transgenes at single copy within a defined and well characterized chromosomal position, ROSA26. This has enabled the direct comparison of constructs from within the same genomic context and allows a systematic and quantitative assessment of the strengths of the promoters in comparison with the endogenous ROSA26 promoter. The behavior of these exogenous promoters, when integrated at ROSA26 in both sense and antisense orientations, reveals a large variation in their levels of activity. In addition, a subset of promoters, EF1α, UbC and CAG, show an increased activity in the sense orientation as a consequence of integration. Transient transfection experiments confirmed these observations to reflect integration dependent effects and also revealed significant differences in the behaviour of these promoters when delivered transiently or stably. As well as providing an important reference which will facilitate the choice of an appropriate promoter to achieve the desired level of expression for a specific research question, this study also demonstrates the suitability of the cassette exchange methodology for the robust and reliable expression of multiple variant transgenes in ES cells.